Inventory management and financial performance of the pharmaceutical segment of GlaxoSmithKline Bangladesh Limited - Abir, Md. Iftehajur Rahman (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.